Additions to the Neoserica calva group from continental South East Asia (Coleoptera: Scarabaeidae: Melolonthinae: Sericini) - Ahrens, Dirk; Pham, Phu Van (Zootaxa, 2021)
In this paper we revise the species of the Neoserica calva group from continental South East Asia, which was so far known only from China. Here we describe 11 new species from Laos, Thailand, and Vietnam: Neoserica allosigillata Ahrens & Pham, new species, N. axelkalliesi Ahrens & Pham, new species, N. chetaoensis Ahrens & Pham, new species, N. diplospinosa Ahrens & Pham, new species, N. fragilis Ahrens & Pham, new species, N. ihlei Ahrens & Pham, new species, N. judsoni Ahrens & Pham, new species, N. peregovitsi Ahrens & Pham, new species, N. rufoplagiatoides Ahrens & Pham, new species, N. sharkeyi Ahrens & Pham, new species, and N. tramton Ahrens & Pham, new species.